2006
DOI: 10.1007/s11136-006-0037-5
|View full text |Cite
|
Sign up to set email alerts
|

Girls growing through adolescence have a higher risk of poor health

Abstract: Introduction: Self rated health, in adult population, is strongly associated with mortality and life expectancy. In younger people this association is less evident, but it may anticipate a similar risk in adult life. Our research, based on the HBSC (Health Behaviour in School-Aged Children) International collaboration, contributes to deepen the knowledge in this field by monitoring adolescents' health through a multinational survey involving 29 European countries, plus North America (Canada and USA) and Israel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
97
3
12

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(144 citation statements)
references
References 24 publications
32
97
3
12
Order By: Relevance
“…Analysis by gender and age differences confirms known existing results 6 , that is lower self-rated health among girls and a decreasing rating with age; this finding underlines the reliability and consistency of our data.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Analysis by gender and age differences confirms known existing results 6 , that is lower self-rated health among girls and a decreasing rating with age; this finding underlines the reliability and consistency of our data.…”
Section: Discussionsupporting
confidence: 90%
“…Cavallo et al 6 reported a gender by age interaction in self-rated health, with girls reporting poorer health across ages 11 to 15.…”
Section: Introductionmentioning
confidence: 99%
“…In line with other research, girls consistently rated their health lower than boys. A large international study on adolescents’ health-related factors revealed that girls have a poorer perception of their health in comparison to boys, at all ages, and in all 29 countries surveyed [4]. Vingiliset al [49] found that youth 12–19 years of age in the top quintile (20%) of body mass index had lower health ratings.…”
Section: Discussionmentioning
confidence: 99%
“…Self-rated health is a subjective, change-sensitive measure of health which covers the ability to function in physical, social, and psychological contexts [2,3]. Adolescents’ self-rated health is related to a number of factors, beginning with sociodemographic factors, such as age, gender, family, and socioeconomic status [47]; followed by health-related behavior, such as mental health [7]; and ending with social environment [6]. …”
Section: Introductionmentioning
confidence: 99%
“…These tendencies have been shown both in somatically ill and general child and adolescent populations. Socio-economical status (SES) seems to have no effect on agreement [4,31].…”
Section: Introductionmentioning
confidence: 99%